2017
DOI: 10.5194/acp-17-2035-2017
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of trans-boundary transport to summertime air quality in Beijing, China

Abstract: Abstract. In the present study, the WRF-CHEM model is used to evaluate the contributions of trans-boundary transport to the air quality in Beijing during a persistent air pollution episode from 5 to 14 July 2015 in Beijing–Tianjin–Hebei (BTH), China. Generally, the predicted temporal variations and spatial distributions of PM2.5 (fine particulate matter), O3 (ozone), and NO2 are in good agreement with observations in BTH. The WRF-CHEM model also reproduces reasonably well the temporal variations of aerosol spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 74 publications
3
41
0
Order By: Relevance
“…Figure 1 shows the WRF-Chem Model simulation domain, and Table 1 provides the model configurations. A detailed model description can be found in Wu et al (2019).…”
Section: Wrf-chem Model and Configurationmentioning
confidence: 99%
“…Figure 1 shows the WRF-Chem Model simulation domain, and Table 1 provides the model configurations. A detailed model description can be found in Wu et al (2019).…”
Section: Wrf-chem Model and Configurationmentioning
confidence: 99%
“…In recent years, China has been suffering from severe haze pollution in winter -especially over the Beijing-Tianjin-Hebei (BTH) region (Guo et al, 2014;Chang et al, 2016). Observations have shown that OAs play a critical role in haze pollution in China (Xing et al, 2013;Sun et al, 2013;Huang et al, 2014;. Huang et al (2014) reported that OA accounted for 30 %-50 % of the PM 2.5 mass in four megacities in China during severe haze days, with the SOA contribution ranging from 44 % to 71 % in winter.…”
Section: Introductionmentioning
confidence: 99%
“…3b). In winter, the insolation is weak in the north of China, unfavorable for the O 3 photochemical production, so the O 3 level is substantially influenced by the boundary conditions Wu et al, 2017). Hence, one of possible reasons for the O 3 underestimation might be from the uncertainty in the O 3 boundary conditions.…”
Section: Model Performancementioning
confidence: 99%